Including the Exclusivists in Interfaith. Issue 3 (3rd July 2018) - Patton, James
Abstract: Ultra-conservative religious actors can be marginalized in interfaith engagements, leading to isolation and contributing to more extremist ideologies. The challenge of engaging these exclusivist and fundamentalist voices, which are often resistant to working across religious lines, is significant. Understanding how religion impacts social spaces and individual decision-making, and working to identify key influencers, can prove essential to overcoming these hurdles and effectively drawing these communities into constructive dialogue.